Modern mechanical surface treatment [ states, stability, effects - Schulze, Volker; Schwing, J. K. (Wiley-VCH, 2006)
The only comprehensive, systematic comparison of major mechanical surface treatments, their effects, and the resulting material properties. The result is an up-to-date, full review of this topic, collating the knowledge hitherto spread throughout many original papers